The Changing Face of Social Consciousness in Singapore: An Interview with Ann Wee - Wee, Ann (Institutional Knowledge at Singapore Management University, 2009)
Social consciousness and the provision for social needs have grown in Singapore, creating an urgency to develop creative ways to keep meeting evolving needs. Having made Singapore her home for 59 years, social work veteran Ann Wee shared with Social Space interesting snippets of her early life in Singapore, in the midst of sharing her views on the rapid changes taking place in the social sphere.